(untitled) (Revista de Psicología, 2021)
The present investigation arises as a result of the inquiry on Emotional Intelligence in the light of the different constructs of the Personality proposed by Eysenck. For this, the E.I. variable measured through TMMS-24 (Fernández-Berrocal et al., 2004) has been correlated with the different variables in which the dimensions of the Personality are manifested, namely: Extraversion, Neuroticism and Psychoticism, obtained by means of the EPQ-RA instrument (Squillace et al., 2013); both data were extracted from a sample of adults of both sexes of Gran Buenos Aires and C.A.B.A., who were in turn administered a sociodemographic survey, all of them virtually (n=215). Regarding the results, significant positive correlations have been obtained between Emotional Attention and Neuroticism, as well as with Emotional Reparation and Extraversion. Likewise, significant negative correlations were found between Emotional Clarity with Neuroticism and Psychoticism, and in Emotional Reparation and Neuroticism.